ภาวะซึมเศร้าของผู้ปกครองและสัมพันธภาพในครอบครัวของเด็กโรคไตเรื้อรัง ในคลินิกโรคไต โรงพยาบาลจุฬาลงกรณ์ - สกาวรัตน์ ตั้งจิตถนอม (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this cross-sectional descriptive study was to examine depression, family relationships and related factors of depression and family relationships of children with chronic kidney diseases in pediatric nephrology clinic of King Chulalongkorn Memorial Hospital. Data were collected from 310 parents by using self reported questionnaires consisted of demographic data ,children’s illness data , family relation data ,Beck Depression Inventory I (BDI-IA) and Family Relationships Test. Data was analyzed by descriptive statistical methods including mean, mode, percentage, frequency, standard deviation ,Pearson’s product moment correlation coefficient. The results showed that 42.6% of parents were under depressed and 22% had mild depression. Family relationships were within good level (92.6%). The commitment and communications were in moderate level while the caring and optimal family role were in good level. It was found that there was mild depression in families with relationships. These findings in order to prevent depression and supported promoting good family relationships.